Variations in accumulated-training load parameters and locomotor demand with consideration of puberty in elite young soccer players - Nobari, H.; Shemshaki, H. K.; Kamis, O.; Oliveira, R.; González, P. P.; Mainer-Pardos, E. (Biology, 2022)
Simple Summary Scientific research has demonstrated that puberty status has a crucial influence on soccer players, and their energy demands are primarily determined by their aerobic capacity. In our investigation, we examined the relationships between maturation variables such as peak height velocity (PHV) and maturity offset with variations in accumulated-training load parameters and locomotor demands in elite young soccer players; the aim was to predict the percentage of changes in their performance ability with adjustments to the training load parameters considering maturation variables. Our study`s main findings revealed a link between accumulated-training load parameters and locomotor demands. In addition, the acute:chronic workload, training monotony, and PHV values explained aerobic power performance. This study offers new valuable insights into the practice of accumulation and motor demand in young elite players.